Evaluation of the Nutritional Value of Insect-Based Complete Pet Foods - Weronika Jacuńska; Wioletta Biel; Krzysztof Zych (Applied Sciences)
Since the legalization of insect protein in pet food, a variety of products incorporating this ingredient have emerged on the market. Although edible insects are acknowledged for high protein content, chitin can also elevate the quantity of indigestible carbohydrates. The objective of this study was to evaluate the nutritional adequacy of fourteen complete dog foods containing edible insects in accordance with the FEDIAF nutritional guidelines. Due to the use of insects as the predominant animal component in all diets, analyses of dietary fiber fractions were carried out to estimate the content of indigestible carbohydrates. The analyses included the assessment of chemical composition, calcium, and phosphorus levels and metabolizable energy. The findings were then compared with the data provided by the manufacturers. All diets were found to meet the minimum recommended levels from the FEDIAF nutritional guidelines for protein (18.0 g/100 g DM) and fat (5.5 g/100 g DM). However, discrepancies were noted between the label data and analysis results. The results for the dietary fiber fraction differed from the crude fiber content, which is consistent with the imprecision inherent to the crude fiber determination method. In one food, there was a discrepancy of up to 19.21 g between the NDF fraction and the crude fiber content. Calcium levels were inadequate in two foods, and furthermore, twelve foods exhibited an abnormal calcium/phosphorus ratio. These findings indicate that while edible insects can be a valuable protein source, their inclusion may lead to increased indigestible carbohydrates, potentially causing digestive issues and gastric discomfort in dogs.